2015
DOI: 10.1155/2015/965475
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Channel Polling Mechanisms for the MAC Protocols in Wireless Sensor Networks

Abstract: Most research done on the channel polling mechanisms for WSN MAC protocols has focused on achieving efficiency in terms of optimizing either delay or energy performance. This study introduces the mechanism of altering the polling interval distribution for the MAC protocol, based on the application's optimization objective (delay or energy). Two options have been considered for both packet interarrival and polling interval distributions: deterministic and exponential, and their impact on performance analysis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast, when deterministic polling process was used for both arrival distributions, it was found that the delay reduced but the energy consumption increased; hence a trade-off between two parameters was found upon comparing deterministic and exponential polling processes. These results were published in [74] and delay plots have been shown in Fig. 3.…”
Section: M2: Developing Proof Of Conceptmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, when deterministic polling process was used for both arrival distributions, it was found that the delay reduced but the energy consumption increased; hence a trade-off between two parameters was found upon comparing deterministic and exponential polling processes. These results were published in [74] and delay plots have been shown in Fig. 3.…”
Section: M2: Developing Proof Of Conceptmentioning
confidence: 65%
“…At this stage, the researchers should be able to identify the differences between the two sets of results and justify any differences. We performed a high-level comparison of the results published in [74] and [13] to have an insight about the differences/similarities in the expected and achieved results. The comparison showed that there was a contradiction between the expected and obtained results.…”
Section: M5: Comparing Detailed Implementation With Preliminary Simul...mentioning
confidence: 99%
“…Although, by increasing the time interval between two poll periods, the number of polls is decreased, and thus the network energy consumption is saved, having long time intervals between these two polling phases increases the energy wastage of the network. Hence, although this issue has been addressed in some researches [ 37 , 196 , 197 ], finding an equilibrium time interval in polling MAC protocols remains a critical issue. Token pass timing In MAC protocols which operate based on the token passing method, the controller node allocates a time interval for passing the token frame to all nodes.…”
Section: Open Issues and Research Challenges For Energy Harvesting Mac Protocols Within Iot Systemsmentioning
confidence: 99%